Discover Constable and The Hay Wain - Riding, Christine; McMahon, Mary 1987- (National Gallery Global, 2024)
"This publication tells the story of [The Hay Wain] and its social, political and art historical significance. It begins by examining artistic depictions of rural England and explores how the country's landscape was changing physically and politically at the turn of the nineteenth century. Other chapters consider Constable's life and career prior to producing The Hay Wain; the making of the painting itself; the work's exhibition in Britain and internationally; and its influential afterlife. Providing fresh perspectives on this celebrated painting, the book illuminates the establishment of Constable as a central figure in the history of British art."-- Publisher's website
Published to accompany the exhibition held at The National Gallery, London 17 October 2024 - 2 February 2025
Keywords: Constable, John -- 1776-1837; Constable, John / 1776-1837 / Hay wain / Exhibitions; Constable, John / 1776-1837 / The Hay Wain; Ausstellungskatalog -- The National Gallery -- 17.10.2024-02.02.2025 -- London